The Meaning of Meaning in the Law - Michael L. Geis (Washington University Law Quarterly, 1995)
The Court uses the words mean and meaning in a number of ways. The difficulty with this is that there are two senses of these words that can, and often are confused, and these are what we have been calling "conventional meaning" and "contextual significance." Locutions containing mean that are particularly problematic, for mean that is sometimes equivalent to 'entail' and sometimes to 'implicate.' Clearly it is in the interest of the Court to be more explicit about what it means by mean and meaning. Unfortunately, its practice of adding modifiers like common, ordinary, natural, every day, and plain not only does not make its meaning clearer, it further exacerbates the problem. The Supreme Court would be well-advised to adopt the analytic techniques of linguists, specifically semanticians and pragmaticians. Rather than the question-begging usage of dictionaries, the Court could employ entailment tests of the sort used here to determine the conventional meaning of the language of disputed texts. Arguably, it would come up with results that not only are more empirically sound, but provide a stronger basis for its real task-to determine the applicability or import, i.e., the contextual significance, of the legal texts that the Court interprets.
Keywords: Linguistics; Law -- Interpretation & construction